Perspektif Siswa Sekolah Dasar Adiwiyata mengenai Perilaku Peduli Lingkungan Hidup: Sebuah Studi Mixed-methods Concurrent Explanatory - Febriyanti, Dinni Asih; Rahmandani, Amalia (Jurnal Teknologi Lingkungan, 2024)
Pro-Environmental Behavior (PEB) has been proven to correlate with some individual positive qualities so it is important to be developed since childhood. The establishment of PEB for early age students is in accordance with the elementary school education curriculum and is supported by the implementation of the Adiwiyata Program. As contrary, student’s knowledge and behavior fall short of expectation. However, this limitation was seldom understood from students perspective, which was still rarely studied. This study was conducted to gain a comprehensive understanding of PEB among students in an elementary school that implements the Adiwiyata Program, using a mixed-methods and concurrent explanatory study. The quantitative study involved 59 students mainly to examine the relationship between knowledge and PEB, while the qualitative study involved 9 students. The result showed that there was no relationship between knowledge and PEB (Spearman's rho=0.103; p=0.436). Thematic and correspondence analysis of qualitative data resulted that the breadth of students' knowledge only met three of six aspects of PEB, successively from the largest: vicarious behaviors toward conservation, recycling, and waste avoidance. This study supports the application of social learning theory in the formation of PEB regarding the importance of the synergy of individual determinants (including outcome expectancies and self-efficacy), the environment, and the behavior. Students had limited control which was largely determined by the environmental role. The dynamics were more complex when students seemed to have control but felt conflicted because they should fulfill needs that did not actually support PEB. Implications for practice and future studies are discussed further.   Abstrak Perilaku peduli lingkungan hidup atau Pro-Environmental Behavior (PEB) terbukti berkorelasi dengan sejumlah kualitas positif individu sehingga penting untuk dibangun sejak masa kanak-kanak. Pembentukan PEB bagi siswa sejak dini bersesuaian dengan kurikulum pendidikan sekolah dasar dan didukung penyelenggaraan Program Adiwiyata. Di sisi lain, wawasan dan perilaku siswa jauh dari harapan. Namun keterbatasan ini kurang dipahami dari perspektif siswa yang masih jarang diteliti. Penelitian ini bertujuan mendapat pemahaman komprehensif tentang PEB siswa di sekolah dasar yang menyelenggarakan Program Adiwiyata, menggunakan penelitian eksplanatori pendekatan campuran dan konkuren. Studi kuantitatif melibatkan 59 siswa terutama untuk menguji hubungan antara pengetahuan dan PEB, sedangkan studi kualitatif melibatkan 9 siswa. Hasilnya menunjukkan tidak ada hubungan antara pengetahuan dan PEB (Spearman’s rho=0,103; p=0,436). Analisis tematik dan korespondensi pada data kualitatif menghasilkan bahwa cakupan wawasan siswa hanya memenuhi tiga dari enam aspek PEB, berurutan dari yang terbesar: perilaku yang mewakili usaha konservasi, daur ulang, dan peniadaan limbah. Penelitian ini menunjukkan pentingnya faktor individu (termasuk harapan akan hasil dan efikasi diri), lingkungan, dan perilakunya yang saling mendukung. Penyelenggaraan program diharapkan dapat melibatkan semua siswa, menggunakan model edukasi yang menarik, menggunakan sarana prasarana terjangkau, melibatkan kerjasama orang tua, menetapkan target capaian, memonitor, menindak lanjuti hingga mengapresiasi keberhasilan siswa.